Why study economic problems? - Tulloss, James Otis (My University, 1899)
Introduction: Evolution of thought is as inevitable as is the evolution of plants, animals, or individuals. Only a few years ago, it was the idea of the colleges of the land, to teach Latin, Greek, French, German and the wise men of those days they thought that these subjects were of the greatest importance to the student as they tended to develop his mind and give him a classical and literary education. But today through a combination of circumstances, the people are beginning to see the value of a new field of study. The scholars of today recognize the value of the above named studies as mind trainers and as developers of the reasoning power, but they also see that there is also another very important problem before us, and that is how to meet and solve successfully the great question of everyday life as they present themselves to each of us.
Citation: Tulloss, James Otis. Why study economic problems?. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Evolution of Thought; Education of Kansas Farmer; Trusts; Theses; Manuscripts (documents)